Implementation of the Policy Merdeka Belajar: A Study at SMA Negeri 1 Pacitan Regency - Senatama, Gandung; Annshori, Muhammad Faqih (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This article finds a discussion to follow-up implementation of the merdeka belajar policy in Indonesia. Through the merdeka belajar or can be interpreted as freedom to learn is a concept that aims to create freedom of thought and innovation. Currently, 100 percent of high scholl, vocational and junior high school levels throughout East Java implement SMIs for the 2023/2024 academic year. Since its estabilishment in Pacitan Regency at the senior high school, there have only been 8 public and private high school out of a total of high schools. The method in this article is a descriptive qualitative analysis. Data collection techniques are carried out by an interview process then see the suitability and match between theory and facts in the field. The results of this article found that the first component of policy implementation from Edward III, namely communication is which occurred at SMA Negeri 1 Pacitan Regency has been going well even though there is often a different understanding of information from the center because of a person’s interpretative power. In the bureaucracy, the branch of the East Java Provincial Education Office through supervisors monitors the implementation. Regarding resources, although it seems sudden because the process of socializing this curriculum is fast, the resources at SMA Negeri 1 Pacitan Regency are fast to make adjusments. Furhermore, the disposition even though inistially ther was no funding for the merdeka belajar curriculum, the school finally decided with the committee to use the BOS fund and Committee Fun for learning purposes